Participation of Jambi Malay Traditional Institutions in Strengthening Election Integrity Through Efforts to Prevent Money Politics - Sri Wahyu Ananingsih; Aju Putrijanti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Elections in Indonesia are still colored by money politics. Money politics is included as a serious election violation because it is considered to injure or damage democracy. Therefore, repressive and preventive efforts are needed so that money politics can be avoided. This study examines the role of the Jambi Malay Customary Institution in efforts to prevent money politics in elections. This study is interesting, because it is rare to find a customary institution making efforts to prevent money politics in elections. The urgency of this study can be used as a pilot model for money politics prevention efforts for other regions This study is a qualitative research using a socio-legal approach. The data used includes primary data and secondary data. Furthermore, all data is analyzed qualitatively. From the results of this study, it can be concluded that the participation of the Jambi Malay Customary Institution includes conducting political education to the community through various customary meetings, developing the Jambi Customary Law, one of which is socializing the provisions of "prohibition of bribery in customs and sharia", increasing the capacity of human resources of its members, encouraging the community and traditional leaders to play a role as participatory supervisors of elections and receiving reports of violations The politics of money from the citizens of the community